Implementation of EMKM Accounting Standards and Its Determinants in Improving MSME Financial Performance - Kuntari, Yeni; Purwantini, Cornelio; Aditya, Elma Muncar; Nuristya, Emmarani (International Journal of Social Science and Business, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economic resilience, particularly during crises such as the 1997 recession and the COVID-19 pandemic. However, the implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) remains limited despite its importance in improving financial transparency and sustainability. Previous studies show inconsistent findings regarding the influence of MSME actors’ perceptions and accounting understanding on the adoption of SAK EMKM, revealing a research gap in local contexts such as Sembungharjo Village, Semarang City. This study aims to examine the effect of MSME actors’ perceptions and accounting understanding on the implementation of SAK EMKM. Using a quantitative approach, data were collected from 90 MSME respondents through questionnaires and analyzed using multiple linear regression. Validity, reliability, and classical assumption tests confirmed that the data met statistical requirements. The findings show that both the perception of MSME actors and accounting understanding have positive and significant effects on the implementation of SAK EMKM. This suggests that enhancing MSME actors’ understanding and perception of accounting standards can improve compliance with SAK EMKM and financial reporting quality. The study highlights the need for continuous socialization and training to strengthen MSMEs’ financial literacy and promote sustainable business practices.